Agroecological features of the influence of microbial preparations on quantitative parameters of grain quality of winter triticale - Писаренко, П. В.; Москалець, В. В. (Scientific Progress & Innovations, 2013)
A study on the sensitivity of winter triticale on the action of microbiological preparations albobakterin and diazobakterin in terms of quality grain has been conducted. It is established that the use of microbial preparations in on winter triticale allowed to differentiate varietal composition of this culture in terms of sensitivity to the action of microorganisms: sensitive (on diazobakterin: «Аmphidiploids 256», «Slavetne»; on albobakterin: «Vivate Nosivsky», «Jaguar», «Augusto», «Slavetne»), moderately sensitive (on diazobakterin: «Augusto») and insensitive (on diazobakterin: «Vivate Nosivsky», «Jaguar», «DAU 5»; on albobakterin: «Аmphidiploids 256», «DAU 5»), depending on the actions of certain biological preparations for a specific grade.